Insights into real-world treatment of cluster headache through a large Italian database: prevalence, prescription patterns, and costs. Issue 9 (2nd September 2021) - Piccinni, Carlo; Cevoli, Sabina; Ronconi, Giulia; Dondi, Letizia; Calabria, Silvia; Pedrini, Antonella; Maggioni, Aldo P.; Esposito, Immacolata; Addesi, Alice; Favoni, Valentina; Pierangeli, Giulia; Cortelli, Pietro; et al.
ABSTRACT: Objective : This study aimed at estimating the treated cluster headache (CH) prevalence and describing prescription patterns and direct costs paid by the Italian National-Health-System. Methods : Through the ReS database (healthcare administrative data collection of a large sample of the Italian population), adults in treatment for CH (acute therapy with sumatriptan/subcutaneous or oxygen, associated with preventive therapy with verapamil or lithium) were selected. A cross-sectional analysis described the prevalence of CH-treated subjects repeated annually in 2013–2017. A longitudinal analysis of patients selected in 2013–2015 and followed for 2 years provided the prescription patterns. Results : The annual prevalence of CH-treated patients increased from 6.4×100, 000 adults in 2013 to 6.7 in 2017. In 2013–2015, 570 patients (80.7% M; mean age 46) treated for CH were found. In 50.4%, the identifying CH treatment was sumatriptan/subcutaneous+verapamil. During follow-up, >1/3 changed the preventive drug and interruption was the most frequent modification, although acute treatments were still prescribed. The mean annual cost/patient ranged from €2, 956 to €2, 267; pharmaceuticals expenditure represented the 56.4% and 57.3%, respectively. Conclusions : This study showed an important unmet need among CH patients, carrying a high economic burden that should be considered in the evaluation of the impact of incoming therapies (e.g. Calcitonin-Gene-Related-Peptide antibodies).